Pembinaan Organisasi Dalam Peningkatan Kinerja Aparatur Pada Kejaksaan Negeri Kendari - Khatimah, Husnul; Justawan, Justawan; Rahman, Rahman (Universitas Halu Oleo, 2021)
This study aims to determine and describe organizational development in improving the performance of the apparatus at the Kendari state prosecutor's office, this study uses descriptive qualitative methods to 11 informants determined by snowball sampling technique, data analysis techniques consist of data collection, data reduction, presentation data, drawing conclusions/verification, the data obtained were analyzed qualitatively and described in descriptive form.Â The results of this study indicate that organizational development in improving the performance of the apparatus at the Kendari State Attorney (Kejari) has been very good, this can be seen from human resources, namely in its development. has been implemented with standard operating procedures so that employee performance has been quite good, the response and behavior has been very good, this can be seen in several cases handling processes that are in accordance with what has been determined by the Prosecutor's Office. flexible, accountable, and reliable behavior, organizational behavior is also very good and organizational structure but the performance of the apparatus at the Kendari District Attorney has not been effective as a whole, this can be seen in the implementation of tasks that are already quite good but in terms of work quality, quantity work and responsibilities still need to be improved regarding the quality of work that needs to be improved again, one of which is in terms of the process of resolving or handling cases, the quantity of work also needs to be increased in the process of accuracy in carrying out tasks so that mistakes or errors do not occur again, and for responsibility need to be improved again because employees especially in the field of coaching have a small number of employees so that the responsibilities given may not necessarily be carried out properly because the shortage of staff has not run effectively as a whole.